Discussion on Art Education In Building a Healthy China and Improving The Level of Social Services - Yan , Yan (International Journal of Management and Education in Human Development, 2022)
Since the founding of New China, especially since the reform and opening up, the Chinese government has always regarded education as one of the most important tasks. Today, China has created a relatively complete education system, higher education, secondary education, primary education, preschool education, etc., as well as a variety of adult education, vocational education, continuing education, and so on. As an important part of the education system, art education also plays an important role. Especially with the construction and development of Chinese society, coupled with the changes in people's ideological concepts, more attention is paid to the art education of young children and the art education of the elderly. This is of extraordinary significance for building a healthy China and improving the level of social services. Children can combine their interests and hobbies, participate in their favorite art education, cultivate artistic literacy, enhance comprehensive quality, and lay a good foundation for a colorful life; and the art education of the elderly group not only highlights the Chinese government's concern for the physical and mental health of the elderly, allowing them to enrich the spiritual world, exercise their bodies, and spend their old age in peace, but also is an important measure to improve social services, improve social service levels, and enhance people's sense of happiness and gain.